Gerald I. Zatuchni, Comp., Post-partum Family Planning, Nueva York, McGraw-Hill Book Company, 1970, 477 p. - Porras Macías, Agustín (Estudios Demográficos y Urbanos, 1972)
GERALD I. ZATUCHNI, Comp., Post-partum Family Planning, Nueva York, McGraw-Hill Book Co., 1970.